Institutional beliefs: validation of an instrument for the health sector - Salazar Botello, Carlos Mauricio; Chiang Vega, María Margarita; Muñoz Jara, Yohana Andrea (Estudios de Administración, 2013)
As far as the beliefs behind behavior are known we will be able to explain the reasons why people behave the way they do. The purpose of this study is to validate a scale to determine institutional beliefs in the healthcare industry. This scale is formed by 39 indicators, representing two dimensions, culture of control (18 items) and culture of development (21 items). This instrument was applied to a 330 subjects sample from different levels and departments of a high complexity hospital. Reliability analyses were assessed using Cronbach’s Alpha, Factor Analysis and calculating eliability for each of the factors. The Alpha coefficients for each of the sub-scales were satisfactory (0.749 and 0.858 respectively). A principal components analysis using Varimax rotation showed 6 factors for the culture of control scale, and 6 factors for the culture of development scale. We concluded that both scales have a satisfactory level of reliability.